Evaluating the Implementation of the Discovery Learning Model in Physics at SMA Negeri 6 Makassar - Reski Sudirman; Kaharuddin Arafah; Bunga Dara Amin (Jurnal Pendidikan Fisika, 2020)
This study aims to evaluate the feasibility of the discovery learning model in physics at SMA Negeri 6 Makassar. In addition to knowing the factors that become obstacles and supporters in applying the learning model in the physics at SMA Negeri 6 Makassar. To achieve these objectives, research has been conducted with a qualitative approach. The subject of this research is the physics teacher at SMA 6 Makassar who already has an educator certificate. Research data collection using observation techniques, interview guidelines and documentation. Data were analyzed using the Miles and Huberman technique consisting of data reduction, data presentation, conclusion drawing and verification. The results showed that the implementation of the discovery learning model in physics had been implemented well. This inhibiting factor is that the application of discovery learning models requires more time allocation, students' characteristics, and teacher consistency in applying the dyscovery learning model. While the supporting factors of this research are the availability of facilities and infrastructures in implementing certain discovery learning models, such as learning media in the form of LCD projectors, internet facilities to facilitate students in gathering information, 2013 curriculum package books provided in school libraries.